1991
DOI: 10.1046/j.1537-2995.1991.31191096180.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of saline‐adenine‐glucose‐mannitol‐suspended red cells in a new plastic container: polyvinylchloride plasticized with butyryl‐n‐ trihexyl‐citrate

Abstract: Blood collection and component preparation have been performed in integrally connected multiple plastic containers made with a new plastic. This polyvinylchloride (PVC) container plasticized with butyryl-n-trihexyl-citrate (BTHC) is a new material for blood storage; it contains no di(2-ethylhexyl)phthalate (DEHP). After removal of plasma and buffy coat, the red cells were suspended in saline-adenine-glucose-mannitol (SAGM) medium. After 42-day refrigerator storage, the total adenine nucleotide concentration re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 16 publications
4
35
2
3
Order By: Relevance
“…Many parameters indicated that, overall, RBCs stored in BTHC-plasticized bags showed poorer membrane preservation capacity than those in DINCH- or DEHP-plasticized bags. A previous study from 1991, found that overall RBC quality in DEHP- and BTHC-plasticized PVC was generally comparable [24]. Our results, focused on events at the RBC membrane, would suggest differently.…”
Section: Discussioncontrasting
confidence: 44%
“…Many parameters indicated that, overall, RBCs stored in BTHC-plasticized bags showed poorer membrane preservation capacity than those in DINCH- or DEHP-plasticized bags. A previous study from 1991, found that overall RBC quality in DEHP- and BTHC-plasticized PVC was generally comparable [24]. Our results, focused on events at the RBC membrane, would suggest differently.…”
Section: Discussioncontrasting
confidence: 44%
“…During a period of 42 days of storage, free hemoglobin/methemoglobin level reaches to 200 mg/ dl [26]. According to the American association of blood banks (AABB) blood or blood products with 1% hemolysis is safe for transfusion, if it provides 75% RBCs in the next 24 h [27].…”
Section: Discussionmentioning
confidence: 99%
“…2,3-BPG was analysed by an enzymatic assay [13] using a test kit (Boehringer-Mannheim, Germany) and Sigma metabolite control (Sigma Diagnostics, USA) in a Cobas Mira S (Roche Diagnostics, Hoffmann-LaRoche, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%